Determination of Hydraulic Ram Pump Performance: Experimental Results - Wanchai Asvapoositkul; Jedsada Juruta; Nattapong Tabtimhin; Yosawat Limpongsa (Advances in Civil Engineering)
The possibility of using a hydraulic ram pump (HRP) as a means of utilizing its energy to produce high head for pump has been investigated. To make such a system economically competitive, it is necessary to improve the performance of HRPs. To achieve this improvement, it is also necessary to understand the parameters that marked out the design of conventional HRPs. The performance is presented in dimensionless terms as the head ratio H∗ or discharge head to drive head and flow-rate ratio Q∗ or discharge flow rate to drive flow rate. The experiments on HRPs were conducted by which each of the following factors could be varied independently: (a) supply head, (b) air chamber pressure, and (c) waste valve beats per minute. An increase in the supply head tends to increase the supply flow rate, delivery flow rate, delivery head, and the overall efficiency of the pump. An increase in air chamber pressure tends to decrease the overall efficiency of the pump. However, there was no significant difference on the HRP performance over a wide range of flow conditions when air chamber pressure was varied. An increase in waste valve beats per minute tends to decrease the supply flow rate, delivery flow rate, and delivery head. But it tends to increase the head ratio, the flow-rate ratio, and the overall efficiency of the pump. The experimental data reveal that the HRP characteristics are functions of the waste valve beats per minute and the supply head.